Ecology and habitats of Serapias perez-chiscanoi (Orchidaceae) near Vila Nova da Baronia (Lower Alentejo, Portugal) - Pereira, Marizia M.D.; Venhuis, Caspar; Gutierres, Francisco (Lazaroa, 2011)
We present the results of the ecology and variation in habitat of the orchid Serapias perez-chiscanoi Acedo, based on field studies between 2002 and 2007. The study area lies in the proximity of the small village of Vila Nova de Baronia, which is situated in the Lower Alentejo province (Portugal). The following climatophilous series of cork oak forest were identified: Asparago aphylli-Querceto suberis sigmetum and their subsequent stages: Phillyreo angustifoliae-Arbutetum unedonis, Halimio ocymoidis-Ericetum umbellatae and/or the community of Ulex australis subsp. welwitschianus and Cistus ladanifer and Trifolio cherleri-Plantaginetum bellardii. Typical communities of wet soils (Junco pygmaei-Isoetetum velati, Periballio laevis-Illecebretum verticillati, Loto hispidi- Chaetopogonetum fasciculati) and saturated soils (Myosotido stoloniferae-Ranunculetum omiophylli and the Juncus bulbosus and Myosotis lusitanica community) were found in depressions. S.perez-chiscanoi was found in the following plant communities: Junco pygmaei-Isoetetum velati, Loto hispidi-Chaetopogonetum fasciculati, Gaudinio fragilis-Agrostietum castellanae, and the community of Ulex australis subsp. Welwitschianus and Cistus ladanifer.